Adaptive Proximal Scaphoid Implant stability despite a perilunate dislocation: a case report - Marcuzzi, Augusto; Vita, Fabio; Sapino, Gianluca; De Santis, Giorgio; Faldini, Cesare; Adani, Roberto (Acta Biomedica Atenei Parmensis, 2021)
Background:We present the case of a 22 y.o. male patient suffering from scaphoid non-union with avascular necrosis of the proximal pole and initial degenerative arthritis.Case report:He referred to our institution with functional impairment and persistent pain (VAS 8\10). The patient underwent the positioning of the small size Adaptive Proximal Scaphoid Implant (APSI), without fixation, through an open dorsal approach and radial styloidectomy. The post-operative course was uneventful, and the patient could resume his daily routine without limitations. 5 years later the patient returned to our department referring a dorsal perilunate dislocation on the same hand. Unexpectedly no implant dislocation occurred and we were able to reduce the perilunate dislocation maintaining the same implant. At 30-month follow-up the patient was pain free (VAS 0\10) with almost completely recovered function of the hand and wrist.Conclusion:In order to minimize implant dislocation, both an adequate scaphoid resection and the choice of the right implant size (which should be lightly downsized compared to the scaphoid resection) are of paramount importance. At the same time, the capsuloplasty should be carefully performed at the right tension, providing adequate stability to the implant. This technique provided satisfactory functional results in a long-term follow-up, even in a young and active patient. Moreover, it does not preclude or complicate the possibility of resorting to different surgical procedures in case of necessity, whilst maintaining the same implant.